An efficient parts-per-million α-Fe2O3 nanocluster/graphene oxide catalyst for Suzuki–Miyaura coupling reactions and 4-nitrophenol reduction in aqueous solution. Issue 3 (19th December 2016) - Wang, Changlong; Salmon, Lionel; Ciganda, Roberto; Yate, Luis; Moya, Sergio; Ruiz, Jaime; Astruc, Didier
Abstract : α-Fe2 O3 nanoclusters supported onto a graphene oxide catalyst are shown for the first time to catalyze Suzuki–Miyaura coupling and 4-nitrophenol reduction in aqueous solution with only parts-per-million loading. Abstract : A new α-Fe2 O3 nanocluster/graphene oxide catalyst is found to be efficient in parts-per-million for Suzuki–Miyaura coupling and 4-nitrophenol reduction in aqueous solution, and this catalyst is recycled at least 4 times in good yields.